Economic and Policy Challenges of the Energy Transition in CEE Countries - Kamiński, Jacek (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
With the announcement of the European Green Deal, which defines a set of policy initiatives aimed at achieving a 50-55% reduction in carbon emissions by 2030 and making Europe climate neutral in 2050, the challenge of energy transition becomes even more critical. The transformation of national energy systems towards sustainability is progressing throughout all Central and Eastern European (CEE) countries, yet the goals and results are different. Most EU Member States have made substantial progress towards meeting their long-term commitments of emissions reductions. However, some bloc members have struggled to meet their obligations. An effective energy transition requires the introduction of appropriately designed policy instruments and of robust economic analyses that ensure the best possible outcomes at the lowest costs for society. In this context, this Special Issue aims to bring into the discussion the challenges that CEE countries have to face and overcome while undergoing energy transition.